EFFECT OF ALGINAT CONCENTRATION VARIATION AND LIPASE CONCENTRATION TO HYDROLYSIS ACTIVITY AND SPECIFIC ACTIVITY OF AMPILE LIPASE IN LIPASE AMOBILIZATION PROCESS FROM Rhizopus delemar - Nani Ratnaningsih (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2004)
Effect of lipasefrom Rhizopus delemar and alginate concentration during immobilization preparation on the hydrolytic activity and the specific activity of immobilized lipase has been studied Immobilization of lipase was done by entrapping lipase onto Ca-ulginate beads with 0.2 M CaC/] Immobilized lipase made from 9 variations bv mixing lipase at same weight with 1%.2 % and 3 % (VI'IV) alginate solution concentration and10 11'1210,ml and 30 ml alginate volume. The stability of immobilizedlipase activity for repeated used reactions were also observed The selected immobilized Iipasefromfirst step wasfree:e driedfor 24, 36 and48 hours. Both the hydrolytic activitv and the specific activity of immobilized lipase were affected hv lipase and alginate concentration. The hydrolytic activity of immobilized lipase decreased with the reduction of lipase concentration, however. the specific activity increased accordingly. After freeze drying, the activity of immobilized lipase was also affected by alginate and lipase concentration. The activity of immobilized liposes were stabil, however, increased afterfreeze drying.